Long Term Patient Reported Outcomes of Tarsal Coalition Resection in Pediatric Patients. Issue 1 (January 2022) - Andrews, Nicholas A.; Torrez, Timothy; Halstrom, Jared R.; Sinha, Tanvee; Pate, James; Agarwal, Abhinav; Conklin, Michael J.; Shah, Ashish
Category: Hindfoot; Midfoot/Forefoot Introduction/Purpose: Tarsal Coalition has been known to be associated with pes planovalgus, unrelenting pain, recurrent sprains, and arthrosis due to an abnormal connection between two or more bones of the feet following failure of segmentation during development. Three entities of coalition exist fibrous, cartilaginous and osseous. Most commonly patients present with pain during activity. On exam range of motion is usually limited and there may be valgus or varus malalignment of the hindfoot. Patients are often offered surgical resection following failure of conservative management. Few large cohort studies exist analyzing complications and patient reported outcomes of pediatric patients undergoing operative treatment. Methods: After IRB approval, patients under the age of 18 undergoing excision of tarsal coalition at a single academic center from 2010-2019 were identified. Medical records were reviewed for variables such as demographics, surgical technique, coalition characteristics, postoperative complications, and coalition recurrence. Patients were contacted via telephone to complete a PROMIS Physical Function and Pain Interference in addition to the Foot Function Index. Contact was attempted at least 3 times before a patient was considered non-respondent. A total of 44 patients and 54 feet were included in the analysis with 17 patients (22 feet) completing patients reported outcomes. Results: The median age at the time of surgery was 12 (IQR 3). Thirty-five feet (64.8%) were from male patients, while 19 feet (35.2%) were from female patients. Pain was the presenting symptom in 49 (90.7%) of feet. Pes planovalgus was present in 25 feet (46.3%). Forty feet (74.1%) had calcaneonavicular coalition compared to 12 feet (22.2%) with talocalcaneal coalition and 2 feet (3.7%) with both. Fibrous coalition was found in 19 feet (35.2%) and the most common. Interposition material was used in 49/54 (90.7%) feet. Wound complications or temporary neuropraxias were seen in 7/54 feet (13.0%), and coalition recurrence occurred in 3/54 feet (5.6%). At a median of 6 years (6.0 IQR) postoperatively, the median postoperative outcomes scores were as follows: PROMIS Physical Function 54.7 (17.9 (IQR)), PROMIS Pain Interference 38.7 (10.0), FFI Pain 14.0 (30.0), FFI Disability 1.0 (9.0), FFI Activity Limitation 3.0 (8.0), and FFI Total 6.0 (12.0). Conclusion: Our study investigated complications and long-term patient outcomes following coalition resection. At follow-up, pediatric patients who underwent excision of tarsal coalition had higher physical function and less pain than the average U.S. population (PROMIS population mean is score of 50). Our recurrence rate of 5.6% is lower than reported in literature. Infection rate was similar to reports in literature at 3.1%. Overall, Coalition resection in pediatrics is a well-tolerated procedure that improves both physical and emotional health.